Тюркизмы в русском языке нa примере ономaстики (зоонимы) - Есбосынов, Е. З.; Ешметовa, Б. Б. (Journal of Oriental Studies, 2018)
There is an attempt made to outline social and cultural relations of the Turkic and Slavic people in the context of language relations. There is brief description of historical and sociolinguistic aspects of the interaction between Russian and Kypchak languages. Soviet Union ethnolinguistic studies (including onomastics) and works of contemporary linguists serve as the main sources